2000
DOI: 10.1128/iai.68.4.2374-2378.2000
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Contributes to Host Defense againstBurkholderia cepaciain the p47phox−/−Mouse Model of Chronic Granulomatous Disease

Abstract: Chronic granulomatous disease (CGD) is an inherited disorder of the NADPH oxidase in which phagocytes are defective in generating superoxide and downstream microbicidal reactive oxidants, leading to recurrent life-threatening bacterial and fungal infections. Xanthine oxidase (XO) is another enzyme known to produce superoxide in many tissues. Using the p47phox؊/؊ mouse model of CGD, we evaluated the residual antibacterial activity of XO. Clearance of Burkholderia cepacia, a major pathogen in CGD, was reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Although our results show decreased oxidative burst and nitrative stress by the majority of monocytes/macrophages of mice lacking NADPH-oxidase, we cannot rule out in vivo formation of oxidative stress via endothelial cell-derived xanthine oxidase and nonphagocytic NADPH-oxidase (42). However, CGD mice are unable to clear infections, presumably because of inadequate generation of in vivo oxidative stress (43). Taken together, we favor the hypothesis that the exuberant inflammatory response in NADPH-oxidase-deficient mice is the main culprit responsible for abolishing the potentially tissue-protective effects of decreased macrophage/monocyte-dependent oxidants.…”
Section: Discussionmentioning
confidence: 59%
“…Although our results show decreased oxidative burst and nitrative stress by the majority of monocytes/macrophages of mice lacking NADPH-oxidase, we cannot rule out in vivo formation of oxidative stress via endothelial cell-derived xanthine oxidase and nonphagocytic NADPH-oxidase (42). However, CGD mice are unable to clear infections, presumably because of inadequate generation of in vivo oxidative stress (43). Taken together, we favor the hypothesis that the exuberant inflammatory response in NADPH-oxidase-deficient mice is the main culprit responsible for abolishing the potentially tissue-protective effects of decreased macrophage/monocyte-dependent oxidants.…”
Section: Discussionmentioning
confidence: 59%
“…Here, we show that, although KatG catalase-peroxidase was important for survival of MTB in wild-type C57Bl/6 mice and in NOS2 -/-mice, which are capable of generating an oxidative burst, it was dispensable for survival in gp91 Phox-/-mice, which cannot produce an oxidative burst. The lack of a discernible phenotype for KatG-deficient MTB in gp91 Phox-/-mice suggests that other potential sources of bactericidal peroxides in vivo, such as p47-dependent/gp91-independent NADPH oxidase (Schaper et al, 2003) and xanthine oxidase (Segal et al, 2000b), cannot compensate for loss of the phagocyte NADPH oxidase. Similar phenotypes have been reported for attenuated ROS-hypersusceptible mutants of Salmo- A and B.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we addressed whether the sequestered PMN may be involved in the mechanism of lung microvascular injury, an important feature of sepsis-induced acute lung injury. To study the in vivo role of NADPH oxidase-derived superoxide, we used p47 phoxϪ/Ϫ and gp91 phoxϪ/Ϫ mice in which the phagocytic cells are incapable of the respiratory burst (11,37). We observed that E. coli challenge of control mice resulted in increases in lung tissue PMN sequestration and migration from 1 to 6 h after the challenge, whereas these responses in the null mice were augmented; for example, transalveolar PMN migration was 40 -50% greater in the NADPH oxidase-defective mice after E. coli challenge than in control mice.…”
Section: Discussionmentioning
confidence: 99%